A new view on bone graft in dental implantation: Autogenous bone mixed with titanium granules - Yeke Wu; Yunqiang Yang; Yuqiao Zhou; Yifei Gu; Xuewei Fu (Wolters Kluwer Medknow Publications, 2013)
Introduction : Dental implants have been widely applied in clinic for many years. However, the success rate is still challenging mainly because of bone deficiency. An ideal bone graft is traditionally thought to guide and induce new bone regeneration as well as been absorbed completely by human body. The Hypothesis: Autogenous bone mixed with titanium granules might be an ideal bone graft for dental implantation. Evaluation of the Hypothesis: First, we analyzed advantages of grafts of autogenous bone mixed with titanium granules, such as serving as a s scaffold for wound healing and tissue regeneration, creating sui microenvironment for implant-bone integration, shortening the new bone's creeping distance, etc. Then we creatively hypothesized a novel alternative bone graft with premixed autogenous bone and non-absorbent titanium granules. Apart from repairing bone deficiency, our hypothesis could promote the integration between new bone and titanium implant from the perspective of microenvironment. We believe that the method is promising and worth extension in clinical application.